Sistem Informasi Permintaan Barang Dan Jasa Fasilitas Umum - Hilman, Mohamad; Hidayanti, Nur; Nuryani, Ely; Budiman, Ramdani (Jurnal Ilmiah Sains dan Teknologi, 2023)
The Banten Province Land Transportation Management Office (BPTD) Region VIII oversees many Service Units (SATPEL) such as type A bus terminals, crossing ports, and weigh stations in Banten Province. The General Bureau is a Work Unit (Satker) tasked with handling requests for goods/services. Some problems occur in the process of requesting goods/services in the Office of the Land Transportation Management Center (BPTD) Region VIII of Banten Province, namely the submission process is still manual, so it takes a long time and the status of approval from each party who has a decision-making policy cannot be known directly. So to overcome the problems faced, it is necessary to design an information system for requests for goods and services that use the Waterfall method and the PHP and MySQL programming languages ​​to create an expected information system, so that data processing can be processed more quickly and in control. Thus each Service Unit (Satpel) can submit a letter of submission of goods by accessing the goods/services procurement web online. Keywords: Service Goods, Demand, Information Systems, Transportation, Waterfall.